Where do differences in theory of mind development come from? An agent-based model of social interaction and theory of mind - Yu, Chi-Lin; Wellman, Henry M. (Frontiers in Developmental Psychology, 2023)
Where do individual differences in theory of mind (ToM) development come from? This is an open-ended issue in developmental psychology. Correlational research suggests social interaction as a cause. However, causal experiments controlling children’s extended, real-life social interactions are impractical and unethical, so the links between social interaction and ToM remain only indirectly demonstrated. To shed light on how social interaction, in different degrees and forms, may influence ToM development, we conducted computational experiments using agent-based modeling. To begin with, we simulated agents (hypothetically, children) and assigned them to ten groups, where each group was manipulated to allow a different amount of social interaction, from 1 to 10. Within each group, agents randomly roamed and encountered one another and then interacted. If these interactions continued long enough, agents’ ToM probabilistically improved. As expected, results showed that the amount of social interaction strongly influenced how fast agents developed ToM, where more social interaction led to more rapid development. Given this confirmation of the assumed link, we more focally explored how other factors – such as having a prior, established social network or agents’ network centrality – could influence the social interaction-ToM link. Then, we tested our model against real-world data from 84 deaf children and showed that our modeling results could explain the social interaction-ToM link observed in deaf children. These demonstrations illustrate how individual differences in ToM development may emerge and offer an explanation specifying a crucial mechanism for how all humans achieve ToM – faster or with delay – through processes of social interaction.